CLUSTER DEVELOPMENT OF MSME SECTOR IN INDIA: AN INTER-STATE ANALYSIS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This paper examines inter-state variation in the  cluster development of MSME sector in India.  The inter-state variations in the parameters of  cluster development (namely Net Working En terprise, Employment, Original Value of Plant  & Machinery, Market value of Fixed Assets and  Gross output) are conceptualized by constructing  a comprehensive Index of Cluster Development.  Empirical evidences suggest that southern, western, and northwestern and some northern states  scores above the average score of all the states. On  the other hand, eastern, central and extreme north ern states (like Jammu and Kashmir) are laggard  behind in the performance of overall development  of MSME clusters. It is therefore predicted that an  inclusive cluster development initiatives across all  regions would strengthen the process of MSME  cluster development in India.
Keywords: MSME; Cluster; Net Working Enterprise; Employment; Original Value of Plant & Machinery; Market value of Fixed Assets; Gross output, India